2020
DOI: 10.1111/mmi.14607
|View full text |Cite
|
Sign up to set email alerts
|

Conformation control of the histidine kinase BceS of Bacillus subtilis by its cognate ABC‐transporter facilitates need‐based activation of antibiotic resistance

Abstract: Bacteria closely control gene expression to ensure optimal physiological responses to their environment. Such careful gene expression can minimize the fitness cost associated with antibiotic resistance. We previously described a novel regulatory logic in Bacillus subtilis enabling the cell to directly monitor its need for detoxification. This cost‐effective strategy is achieved via a two‐component regulatory system (BceRS) working in a sensory complex with an ABC‐transporter (BceAB), together acting as a flux‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…This indicates that the observed activity for the WT protein is less than what is observed for some of the mutants, and what might be observed in a hypothetical state in which the autokinase is unfettered by connections to HAMP and the membrane. Although unexpected, this finding is consistent with a large body of data ( Fernández et al, 2019 ; Wang et al, 2015 ; Koh et al, 2021 ), and has been observed in PhoQ with antimicrobial peptide stimulation ( Matamouros et al, 2015 ). Thus, in ligand-responsive HKs, evolution does not drive toward maximal activity which might lead to wasteful and toxic transcription, but instead a finely tuned value that is titrated to the degree of transcription required for function.…”
Section: Resultssupporting
confidence: 91%
“…This indicates that the observed activity for the WT protein is less than what is observed for some of the mutants, and what might be observed in a hypothetical state in which the autokinase is unfettered by connections to HAMP and the membrane. Although unexpected, this finding is consistent with a large body of data ( Fernández et al, 2019 ; Wang et al, 2015 ; Koh et al, 2021 ), and has been observed in PhoQ with antimicrobial peptide stimulation ( Matamouros et al, 2015 ). Thus, in ligand-responsive HKs, evolution does not drive toward maximal activity which might lead to wasteful and toxic transcription, but instead a finely tuned value that is titrated to the degree of transcription required for function.…”
Section: Resultssupporting
confidence: 91%
“…The activities of the VIPP1/IM30/PspA family of proteins in membrane repair and protection, and in particular the specific role of different oligomeric states, are still debated. Finally, the mechanisms by which diverse CESRs sense membrane perturbations are largely unknown, although considerable progress has been made in the specific cases of the DesK sensor kinase ( Abriata et al, 2017 ), flux-sensing by peptide detoxification modules ( Koh et al, 2020 ), and the lysozyme-mediated induction of the σ V protein ( Ho and Ellermeier, 2019 ). The overall picture is of the cell membrane as a complex and adaptable assemblage of many different lipid and protein species that still has many secrets to reveal.…”
Section: Discussionmentioning
confidence: 99%
“…The BceAB system appears to act in disassembly of bacitracin complexes to confer resistance ( Kobras et al, 2020 ). In addition, BceAB interacts with the BceRS TCS to allow sensing of bacitracin ( Ohki et al, 2003 ; Dintner et al, 2014 ; Fritz et al, 2015 ; Koh et al, 2020 ). The BceRS-AB system provides a first line of defense against bacitracin, with higher levels of antibiotic activating the protective responses mediated by the LiaRS and σ ECF regulons ( Radeck et al, 2016 ).…”
Section: Cell Envelope Stress Responses That Function Through Membrane Proteinsmentioning
confidence: 99%
“…To support this hypothesis, we noticed that several ABC permeases have been described as acting as co‐sensors/receptors of two‐component regulatory systems (Piepenbreier et al ., 2017 ). An interesting example is the ABC permease BceB which acts as an accessory sensor/receptor in the two‐component regulatory pathway controlling the antibiotic resistance system Bce of Bacillus subtilis (Koh et al ., 2020 ). This example is of particular interest, as the histidine kinases of the Vfm and Bce systems both exhibit an atypical topographical organization of their functional domains.…”
Section: Discussionmentioning
confidence: 99%